(3OjhGf GdCOH aj eMGSf HdZGA GdYQHs - (3CMeO Hf eMeO Hf YeQ, TgGH GdOjf GdNaGLj GdeUQj , GdTgGH GdNaGLj,J (B1069 (3g` s ((3Ydj Hf eMeO Hf MSjf Hf fGUQ GdefdG GdMehj GdMfaj s)
(3ChdgG (B:s
(3SHMGfc dG ofMUj KfGA Ydjc bO cfJ Cge Cf CLeY HOGFY GdTYQGA hQhGFY GdocJGH hGdHdZGA, hCcSQ dg OaJQkG jchf SajfI fhM, hLGeY SajGf s
(3BNQgG (B:s
(3ef TYQ deMeO Hf ESeGYjd GdeUQj GdoedbH HGdJGQjN dCYO JaGM GdNOhO HfaSLkG dKekG hcGahQ GdJQGFH YfHQkG s
(3HBNQgG agQSJ HCSeGA ef JQLehG ajgG ef GdCOHGA hjbY aj (B9 (3UaMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B488 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B22 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs